REKAMAN PERISTIWA GEOLOGI KUARTER PADA SEDIMENTASI DAN FLUKTUASI PERMUKAAN AIR DANAU TONDANO PURBA DIDASARI KORELASI UNIT FASIES KUARTER DI TENGGARA DANAU, SULAWESI UTARA - Herman Moechtar (Jurnal Geologi dan Sumberdaya Mineral, 2007)
The Quaternary deposits of lake Tondano consist of Tondano tuff covered by young Volcanic rock and the Quaternary sediments. The Quaternary sediments are divided by lake, sand-lake, tidal-lake, river channel, floodplain, swamp, and flood basin deposits. In general, the sedimentary and fluctuation of lake level processes occurred in active tectonic and tectonism is the main factor controlling their occurrence. The amount of material from eruption, source area and slope gradients were important factors influencing the development of the sedimentary succession in the paleo-lake Tondano.The vertically and laterally different accumulation of sediments during the deposition into the basin, is obviously related to the regional tectonic and local volcano tectonic of the basin. Probably, changes in climatological between more humid to drier conditions occurred from unit of deposition facies II (Ufp.II) to unit of depositon facies III (Uft.III). Keywords:   Facies, sedimentation,  lake water level fluctuation,  tectonic